Research on the Root Cutting Mechanism of Involute Gears Machining Using the Generating Method - Zhang Wei; Hou Keqing; Zhou Yanfang (Jixie chuandong)
By establishing the standard rack tool profile curve equation, using the VB.NET programming language to carry out secondary development in AutoCAD environment, the dynamic simulation program of the whole process of involute gears and root cutting is developed using the generating method to further study and explore the gear root cutting process and root cutting mechanism, and the maximum root cutting radius is accurately solved. The wrong conclusion that the maximum root cutting radius is equal to the distance between the center of rotation of the gear being machined and the intersection point between the top line of the tool teeth and the line of engagement is corrected. Based on this, the limiting conditions of the root cutting to the starting point of the working section of the big and small gear tooth profile and the interference at the root of the big and small gear are redetermined in the closed diagram selected by the displacement coefficient. Then the closure line chart of the modification coefficient selection can be drawn accurately.